KAJIAN YURIDIS MENGENAI LEGALITAS ABORSI DALAM KASUS PEMERKOSAAN SERTA KAITANNYA DENGAN PENGATURAN ABORSI DALAM RUU KUHP (PERBANDINGAN ANTARA TINDAK PIDANA ABORSI DALAM SISTEM HUKUM INDONESIA DAN ABORSI DALAM SISTEM HUKUM SINGAPURA) - Tiara Rahmawati (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2022)
Abortion has been a controversial topic throughout history due to a variety of perspectives. There are pros and there are cons. Including the regulation of abortion in the Draft Law (RUU) of the Criminal Code, where there are provisions and/or Articles on abortion and/or abortion. In the Criminal Code, abortion is regulated in Articles 251, 415, 469, 470, and 471. Then when we look at the act of abortion that is legalized according to the provisions in his country, the real example is in Singapore which is in the Termination of Pregnancy Act Cap. 324 the implementation of abortion is not prohibited. Meanwhile, in the ius constitutum of Indonesia, abortion is a criminal act or crime against life regulated in Articles 229, 346-349, and 535 of the Criminal Code, and regarding the exemption of abortion in Indonesia itself is regulated in Law No. 36 of 2009 on Health. Therefore, this writing, the author intends to legally examine the legalization of abortion in rape cases in Indonesia, which should be in the Criminal Code as a constituent can contain the rules, with a comparison between abortion in Indonesia and abortion in Singapore.